DAMPAK MOTIVASI DAN DISIPLIN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. KEDAMIN JAYA KABUPATEN KAPUAS HULU - Diana, Tri; Amelia, Amelia (Jurnal Ekonomi Integra, 2023)
This research was conducted with the aim of the impact of work motivation and work discipline on work productivity both partially and simultaneously.  Qualitative descriptive method using multiple Linear Regression test (standardized)). The research variability consists of dependent variables, namely work productivity and independent variables, namely work motivation and work discipline. 33 employees made up the sample population (census research) used. The results of the study found that simultaneously motivation and discipline have a significant influence on work productivity. Partially motivation lacks a significant influence on work productivity. And discipline has a significant influence on work productivity.